2007
DOI: 10.1111/j.1745-7254.2007.00703.x
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory effect of dendroaspis natriuretic peptide on spontaneous contraction in gastric antral circular smooth muscles of guinea pigs

Abstract: Aim: To determine whether the natriuretic peptide receptor (NPR) is present in the stomach of guinea pigs and to investigate the effect of dendroaspis natriuretic peptide (DNP) on the gastric motility of guinea pigs and its mechanism. Methods: The distribution of the NPR was analyzed by autoradioimmunography. The spontaneous contraction of gastric antral circular muscles of guinea pigs was recorded by a 4-channel physiograph. The whole cell patch-clamp technique was introduced to record calcium-activated potas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
28
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 18 publications
(29 citation statements)
references
References 21 publications
1
28
0
Order By: Relevance
“…NPs are also secreted from gastric mucosa [14][15][16] . Our previous study indicated that CNP relaxes gastric circular and longitudinal smooth muscles in human, rat and guinea-pig stomach, and that NPRs are distributed in rat gastric smooth muscle layer [17][18][19] . In smooth muscle, CNP activates its cognate NPR-B, which includes an intracellular pGC domain and catalyzes the synthesis of cGMP within the cytosol [20] .…”
Section: Introductionmentioning
confidence: 99%
“…NPs are also secreted from gastric mucosa [14][15][16] . Our previous study indicated that CNP relaxes gastric circular and longitudinal smooth muscles in human, rat and guinea-pig stomach, and that NPRs are distributed in rat gastric smooth muscle layer [17][18][19] . In smooth muscle, CNP activates its cognate NPR-B, which includes an intracellular pGC domain and catalyzes the synthesis of cGMP within the cytosol [20] .…”
Section: Introductionmentioning
confidence: 99%
“…However, there is no report about the effect of DNP on Ca 2+ -activated K + channels, particularly in gastrointestinal SMCs. In a previous study [15], we found that DNP inhibits spontaneous contraction in gastric antral circular myocytes. In the present study, DNP significantly and dose-dependently increases I K(Ca) and STOCs in gastric antral circular SMCs (Fig.…”
Section: Discussionmentioning
confidence: 71%
“…Kim et al [10] have for the first time demonstrated that DNP is present in rat colon and can control colonic motility as a local regulator. We have found that NPs can also regulate gastric motility [11][12][13][14]. Our further study indicates that the regulatory effect of DNP on spontaneous contraction in gastric antral circular SMCs occurs via a cGMP-dependent pathway [15].…”
mentioning
confidence: 62%
“…Evolutionary studies [8] have suggested the presence of DNP-like immunoreactivity in rat colon, and the DNP-like molecule may control colonic motility as a local regulator. Interestingly, we found that DNP inhibits spontaneous contraction in gastric circular smooth muscle [9] . NPs are similar to nitric oxide (NO), which play important physiological functions by affecting the activity of cGMP and cAMP.…”
Section: Introductionmentioning
confidence: 87%